Concentration of Potassium in Plasma, Erythrocytes, and Muscle Tissue in Cows with Decreased Feed Intake and Gastrointestinal Ileus. (15th February 2016) - Schneider, S.; Müller, A.; Wittek, T.
Abstract : Background: Healthy cows consume large amounts of potassium and a sudden loss in appetite can lead to hypokalemia. The routine method to evaluate potassium homeostasis is the measurement of the extracellular potassium in plasma or serum, but this does not provide information about the intracellular potassium pool. Hypothesis/Objectives: To evaluate potassium homeostasis by comparing the extracellular and intracellular potassium concentration in cows with reduced feed intake and gastrointestinal ileus. Animals: Twenty cows 1–3 days postpartum (group 1) and 20 cows with gastrointestinal ileus (group 2). Methods: Observational cross‐sectional study. Plasma potassium was measured by using an ion‐sensitive electrode. Intracellular potassium was measured in erythrocytes and muscle tissue (muscle biopsy) by using inductively coupled plasma optical emission spectroscopy. Results: Cows of group 1 did not have hypokalemia. Overall cows with gastrointestinal ileus were hypokalemic (mean ± SD, 2.9 mmol/L ± 0.78), but potassium concentration in erythrocytes and muscle tissue was not lower than in postpartum cows. Intracellular potassium in erythrocytes varied very widely; group 1: 3497–10735 mg/kg (5559 ± 2002 mg/kg), group 2: 4139–21678 mg/kg (7473 ± 4034 mg/kg). Potassium in muscle tissue did not differ between group 1 (3356 ± 735 mg/kg wet weight) and group 2 (3407 ± 1069 mg/kg wet weight). No association between extracellular and intracellular potassium concentrations was detected. Conclusions and clinical importance: That measurement of plasma potassium concentration is not sufficient to evaluate potassium metabolism of cows.